1994
DOI: 10.1111/j.1600-0560.1994.tb00278.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical expression of BCL‐2 in melanomas and intradermal nevi

Abstract: The BCL-2 gene is the prototype of a newly described family of oncogenes involved in tumorigenesis by blocking apoptosis, or programmed cell death. Overexpression of BCL-2 protein was originally described in follicular B-cell lymphomas bearing the 14;18 translocation. BCL-2 overexpression has also been described in other lymphomas and more rarely in neoplasms outside the lymphoid tissue. The aim of this paper is to determine the immunohistochemical expression of BCL-2 in intradermal nevi and primary invasive a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0
3

Year Published

1998
1998
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(29 citation statements)
references
References 21 publications
3
23
0
3
Order By: Relevance
“…Ramsay et al 26 reported immunohistochemical detection of Bcl-2 in 100% of melanocytes and benign nevi, but found less expression in primary and metastatic melanoma. Similar results were reported by Saenz-Santamaria et al, 27 Collins et al 28 and Cerroni et al 29 The role of the other antiapoptotic proteins, Bcl-XL and Mcl-1 in melanoma is largely unknown. In 1998, Tang et al 20 reported that Bcl-2 was downregulated in melanoma but Bcl-XL and Mcl-1 were upregulated.…”
supporting
confidence: 80%
See 1 more Smart Citation
“…Ramsay et al 26 reported immunohistochemical detection of Bcl-2 in 100% of melanocytes and benign nevi, but found less expression in primary and metastatic melanoma. Similar results were reported by Saenz-Santamaria et al, 27 Collins et al 28 and Cerroni et al 29 The role of the other antiapoptotic proteins, Bcl-XL and Mcl-1 in melanoma is largely unknown. In 1998, Tang et al 20 reported that Bcl-2 was downregulated in melanoma but Bcl-XL and Mcl-1 were upregulated.…”
supporting
confidence: 80%
“…The results of this study are consistent in part with several immunohistochemic and Western blot studies carried out by others 26,27,29,33 over the past decade and are contrary to the concept that Bcl-2 expression is associated with progression of melanoma. Instead, our results show that Bcl-2 expression was associated with a good prognosis, as reported by Divito et al 34 in studies on tissue microarrays.…”
Section: Discussionsupporting
confidence: 34%
“…Negative controls for the staining reactions were obtained by omitting the primary antibodies and substituting them with normal mouse serum. Staining of scattered epidermal basal cells of skin metastases, infiltrating lymphocytes, as well as eccrine sweat glands and dermal papillae of the hair follicles served as positive internal controls for successful immunohistochemistry for Bcl-2 [16, 17, 18, 19, 20]. …”
Section: Methodsmentioning
confidence: 99%
“…The presence of bcl-2 protein has been observed in several benign and malignant tumors of the skin, including melanoma, basal cell carcinoma, Merkel cell carcinoma and T cell lymphoma [23, 24, 25, 26, 27, 28]. Our results showed that bcl-2 protein expression was downregulated after successful treatment not only by intralesional IFN-γ therapy but also by PUVA and radiation therapy, which suggests that the reduced expression of bcl-2 may not be due to a direct effect of IFN-γ: The reduced expression of bcl-2 may result from successful treatments of MF.…”
Section: Discussionmentioning
confidence: 99%